Profiling of the serum MiRNAome in pediatric egyptian patients with wilms tumor - Mohamed, Fatma S.; Jalal, Deena; Fadel, Youssef M.; El-Mashtoly, Samir F.; Khaled, Wael Z.; Sayed, Ahmed A.; Ghazy, Mohamed A. (Frontiers in Molecular Biosciences, 2024)
Wilms tumor (WT) is a pediatric kidney cancer associated with poor outcomes in patients with unfavorable histological features such as anaplasia. Small non-coding RNAs, such as miRNAs, are known to be involved in WT pathogenesis. However, research on the clinical potential of blood-based miRNAs is limited. This study aimed to profile aberrantly expressed miRNAs in WT serum samples, evaluate their potential to differentiate standard-risk patients with favorable histology from those with anaplastic WTs, and assess their clinical value as minimally invasive biomarkers for WT detection. The study used next-generation sequencing (NGS) to analyze miRNA expressions in serum samples from 37 Egyptian children, including 10 healthy individuals, 14 with non-anaplastic WTs (favorable histology FH-WTs), and 13 with anaplastic WTs (unfavorable histology UnFH-WTs). Functional enrichment analysis was conducted to identify critical pathways and biological processes affected by dysregulated miRNAs, and a network was created for the most promising miRNA-target interactions linked to WT. The study identified a distinct miRNA expression signature of 45 miRNAs (3 upregulated and 42 downregulated) in WT serum samples compared to healthy controls, with 29 miRNAs exclusively dysregulated in FH-WTs and 6 miRNAs dysregulated solely in UnFH-WTs. These dysregulated miRNAs displayed significant enrichment in cancer-related pathways, such as PI3K/AKT, FOXO, and MAPK signaling. In relation to WT clinicopathological features, decreased levels of hsa-miR-2355-3p showed a significant positive correlation with clinical stage (r = 0.6597, p = 0.0006) and WT metastasis (r = 0.439, p = 0.021). The ROC curve analysis revealed that multiple dysregulated miRNAs in WT, specifically hsa-miR-7-5p, hsa-miR-146a-5p, hsa-miR-378a-3p, and hsa-miR-483-5p, exhibited high diagnostic potential for WT, with AUC values exceeding 0.86. Among WT histopathology types, the hsa-miR-1180-3p showed a 2.3 log2fold difference in expression between UnFH-WTs and FH-WTs, indicating its potential as a biomarker with 92% sensitivity and 85% specificity for identifying UnFH-WTs. Its target genes were enriched in pathways related to cell division and cell cycle regulation. In conclusion, hsa-miR-1180-3p could be a reliable bloodbased biomarker for distinguishing WT histopathological types,and further research is needed to validate its clinical value.